Fha interaction with phosphothreonine of TssL activates type VI secretion in Agrobacterium tumefaciens. - Jer-Sheng Lin (Public Library of Science (PLoS), 2014)
The type VI secretion system (T6SS) is a widespread protein secretion system found in many Gram-negative bacteria. T6SSs are highly regulated by various regulatory systems at multiple levels, including post-translational regulation via threonine (Thr) phosphorylation. The Ser/Thr protein kinase PpkA is responsible for this Thr phosphorylation regulation, and the forkhead-associated (FHA) domain-containing Fha-family protein is the sole T6SS phosphorylation substrate identified to date. Here we discovered that TssL, the T6SS inner-membrane core component, is phosphorylated and the phosphorylated TssL (p-TssL) activates type VI subassembly and secretion in a plant pathogenic bacterium, Agrobacterium tumefaciens. Combining genetic and biochemical approaches, we demonstrate that TssL is phosphorylated at Thr 14 in a PpkA-dependent manner. Further analysis revealed that the PpkA kinase activity is responsible for the Thr 14 phosphorylation, which is critical for the secretion of the T6SS hallmark protein Hcp and the putative toxin effector Atu4347. TssL phosphorylation is not required for the formation of the TssM-TssL inner-membrane complex but is critical for TssM conformational change and binding to Hcp and Atu4347. Importantly, Fha specifically interacts with phosphothreonine of TssL via its pThr-binding motif in vivo and in vitro and this interaction is crucial for TssL interaction with Hcp and Atu4347 and activation of type VI secretion. In contrast, pThr-binding ability of Fha is dispensable for TssM structural transition. In conclusion, we discover a novel Thr phosphorylation event, in which PpkA phosphorylates TssL to activate type VI secretion via its direct binding to Fha in A. tumefaciens. A model depicting an ordered TssL phosphorylation-induced T6SS assembly pathway is proposed.